Zika-Virus-Encoded NS2A Disrupts Mammalian Cortical Neurogenesis by Degrading Adherens Junction Proteins - Yoon, Ki-Jun; Song, Guang; Qian, Xuyu; Pan, Jianbo; Xu, Dan; Rho, Hee-Sool; Kim, Nam-Shik; Habela, Christa; Zheng, Lily; Jacob, Fadi; Zhang, Feiran; Lee, Emily M.; et al. (Cell stem cell, 2017)
Zika virus (ZIKV) directly infects neural progenitors and impairs their proliferation. How ZIKV interacts with the host molecular machinery to impact neurogenesis in vivo is not well understood. Here, by systematically introducing individual proteins encoded by ZIKV into the embryonic mouse cortex, we show that expression of ZIKV-NS2A, but not Dengue virus (DENV)-NS2A, leads to reduced proliferation and premature differentiation of radial glial cells and aberrant positioning of newborn neurons. Mechanistically, in vitro mapping of protein-interactomes and biochemical analysis suggest interactions between ZIKA-NS2A and multiple adherens junction complex (AJ) components. Functionally, ZIKV-NS2A, but not DENV-NS2A, destabilizes the AJ complex, resulting in impaired AJ formation and aberrant radial glial fiber scaffolding in the embryonic mouse cortex. Similarly, ZIKA-NS2A, but not DENV-NS2A, reduces radial glial cell proliferation and causes AJ deficits in human forebrain organoids. Together, our results reveal pathogenic mechanisms underlying ZIKV infection in the developing mammalian brain. [Display omitted] •ZIKV-NS2A, but not DENV-NS2A, depletes RGCs in the embryonic mouse cortex•ZIKV-NS2A expression causes mis-positioning of newborn neurons in the mouse cortex•ZIKA-NS2A interacts with and depletes adherens junction (AJ) complex proteins•ZIKV-NS2A impairs RGC proliferation and AJ formation in human forebrain organoids Zika virus infects neural stem cells and causes microcephaly. In this study, Yoon et al. showed that NS2A protein encoded by Zika virus, but not by Dengue virus, impairs proliferation of radial glial cells in both embryonic mouse cortex and human forebrain organoids. Mechanistically, ZIKV-NS2A disrupts adherens junction formation.